DAMPAK PERANG RUSIA - UKRAINA TERHADAP EKSPOR BATU BARA INDONESIA KE JERMAN TAHUN 2022 - 2023 - Setiawan, Fajar Ajie; Yudono, Maisa; Alifia, Nadhira (Moestopo Journal of International Relations (MJIR), 2024)
The purpose of this research is to find out how Indonesian coal exports to Germany will be in 2022 to 2023 after the outbreak of war between Russia and Ukraine on February 24 2022. The method used in this research is an explanatory qualitative method, namely by collecting data through literature studies and conducting interviews. with related agencies to provide explanations and analyze the impact of the Russian and Ukrainian wars on Indonesian coal exports to Germany. The theories or concepts used in this research are energy security, economic embargo, exports and energy crisis. The research results explain that in general, the war between Russia and Ukraine had no impact on Indonesia's relations with Germany. However, economically, new opportunities have emerged for Indonesia to export coal to the German market..